Impactos de la integración y especialización sectorial sobre la sincronización entre los ciclos internacionales y el producto agropecuario del Perú - Tello, Mario D. (2010)
This paper estimates the impact of the degree of trade and financial integration, and the sectoraldegree of specialization on the degree of synchronization between the business cycle of agriculturalproduct of Peru and those of the products of 31 Peruvian’s country trade-partners for period1982-2006. Estimations results show the impacts were weak and not robust before differentindicators and estimations methods. Similarly, the estimated impacts of a set of six Peruvian´spreferential trade arrangements upon the same four indicators were not statistical significant.Keywords: synchronization, preferential trade arrangements, commercial and financial integration,sectorial specialization.